SOSIALISASI PENGEMBANGAN UMKM BERBASIS SYARIAH DALAM MENINGKATKAN PENDAPATAN MASYARAKAT DAMANHURI - Ria Andrianie; Aliffia Al Zahra (Journal of Empowerment and Community Service (JECSR), 2022)
Important points that must be considered include MSMEs and Islamic Financial Institutions (LKS). This is because MSMEs are businesses run by small business owners with limited capital but have a significant impact on the Indonesian economy. However, due to their limited production capacity, limited market share, and lack of access to capital, they are a vulnerable business. As a result, real sector business actors and MSMEs need community service programs that can support them through outreach. The purpose of this Community Service Activity (PKM) is to educate the general public about how to cooperate with Islamic financial institutions to establish sharia-based businesses. This PKM activity was carried out with a number of residents of Mugirejo District, especially residents of Jalan Damanhuri, and focused on MSME business actors, especially housewives